Erupsi Gigi Insisivus Pertama Permanen Rahang Bawah Berdasarkan Letak Geografis Pesisir Pantai dan Pegunungan Di Kabupaten Pacitan - Ayun Inesta Putri; Agus Marjianto; Sri Hidayati (Jurnal Ilmiah Keperawatan Gigi, 2020)
Background: The problem in this study is the difference in the eruption of the mandibular first permanent incisor based on the geographical location of the coast and mountains of Pacitan Regency. Purpose:The purpose of this study was to determine the differences in the eruption of mandibular first permanent incisors based on the geographical location of the coast and mountains of Pacitan Regency. Methods:This type of research is analytic observational research with a cross sectional approach. The sample in this study were some students at elementary schools in coastal areas, namely Ngadirojo and Pacitan districts, and elementary schools located in mountainous areas, namely Tulakan and Tegalombo districts, with a minimum sample size of 111 children. The method used for data collection is the method of observation and documentation. The analysis technique used is the chi-square data analysis technique with α = 0.05. Result:The results showed that the data normality test for the mandibular first permanent incisor (31.41) both in mountainous and coastal areas was 0.000 so that sig ≤ 0.05, which indicates that the data is not normal. The chi-square test of dental element 31 shows a sig value of 0.005 so that sig ≤ 0.05 and tooth element 41 a sig value of 0.003 so that sig ≤ 0.05. This means that H1 is accepted, namely that there is a difference in the eruption of the mandibular first permanent incisor based on the geographical location of the coastal and mountainous areas of Pacitan Regency.